Three-dimensional postoperative accuracy of extra-articular forearm osteotomies using CT-scan based patient-specific surgical guides - Vlachopoulos, Lazaros (BMC Musculoskelet Disord, 2015)
BACKGROUND: Computer assisted corrective osteotomy of the diaphyseal forearm and the distal radius based on computer simulation and patient-specific guides has been described as a promising technique for accurate reconstruction of forearm deformities. Thereby, the intraoperative use of patient-specific drill and cutting guides facilitate the transfer of the preoperative plan to the surgery. However, the difference between planned and performed reduction is difficult to assess with conventional radiographs. The aim of this study was to evaluate the accuracy of this surgical technique based on postoperative three-dimensional (3D) computed tomography (CT) data. METHODS: Fourteen patients (mean age 23.2 (range, 12-58) years) with an extra-articular deformity of the forearm had undergone computer assisted corrective osteotomy with the healthy anatomy of the contralateral uninjured side as a reconstruction template. 3D bone surface models of the pathological and contralateral side were created from CT data for the computer simulation. Patient-specific drill and cutting guides including the preoperative planned screw direction of the angular-stable locking plates and the osteotomy planes were used for the intraoperative realization of the preoperative plan. There were seven opening wedge osteotomies and nine closing wedge (or single-cut) osteotomies performed. Eight-ten weeks postoperatively CT scans were obtained to assess bony consolidation and additionally used to generate a 3D model of the forearm. The simulated osteotomies- preoperative bone models with simulated correction - and the performed osteotomies - postoperative bone models – were analyzed for residual differences in 3D alignment. RESULTS: On average, a significant higher residual rotational deformity was observed in opening wedge osteotomies (8.30° ± 5.35°) compared to closing wedge osteotomies (3.47° ± 1.09°). The average residual translation was comparable small in both groups, i.e., below 1.5 mm and 1.1 mm for opening and closing wedge osteotomies, respectively. CONCLUSIONS: The technique demonstrated high accuracy in performing closing wedge (or single-cut) osteotomies. However, for opening wedge osteotomies with extensive lengthening, probably due to the fact that precise reduction was difficult to achieve or maintain, the final corrections were less accurate.